First Neogene skulls of Doedicurinae (Xenarthra, Glyptodontidae): morphology and phylogenetic implications - Zurita, Alfredo Eduardo (2014)
Among Glyptodontidae, Doedicurinae (late Miocene-early Holocene) includes the glyptodonts with the largest size and latest records. Doedicurinae is mainly characterized by a smooth surface of the osteoderms with large foramina, and a particular morphology of the caudal tube. All taxa except one (Doedicurus clavicaudatus) have been recognized and characterized on the basis of remains of caudal tubes and/or dorsal carapaces. This situation produced an evident overestimation of the real diversity of this group, and a taxonomic revision is needed. In fact, no Neogene skulls were known. We present and describe the first two Neogene skulls belonging to Doedicurinae (cf. Eleutherocercus antiquus). The materials come from the El Polvorín and Chapadmalal formations, in the surroundings of Olavarría and Mar del Plata localities, respectively (Buenos Aires province, Argentina). A cladistic analysis was carried out in order to situate these materials among Glyptodontidae and inferring new synapomorphies at skull level in Doedicurinae. Cf. E antiquus clusters with the Pleistocene species D. clavicaudatus showing three unambiguous synapomorphies, which in turn represents the first skull synapomorphies for Doedicurinae. Finally, the presence of cf. E. antiquus in the El Polvorín and Chapadmalal formations suggests that the stratigraphic distribution of this species could include the Montehermosan-Chapadmalalan interval.